REPRESENTASI HEGEMONI DALAM NOVEL MÉMOIRES D’HADRIEN KARYA MARGUERITE YOURCENAR - Laila Fariha Zein; Dadang Sunendar; Tri Indri Hardini (JENTERA: Jurnal Kajian Sastra, 2019)
This writing  aims to analyze and describe the elements of hegemony based on Gramsci's perspective in novel Mémoires d’Hadrien of Marguerite Yourcenar. Gramsci's hegemony is a mastery concept or strategy based on intellectual leadership, moral awareness, and agreement. The method used in this research is the descriptive-qualitative. The instrument used in this research is the bibliographic study and documentation. The population of the research is novel Mémoires d’Hadrien, and the sample of the research is hegemony based on Gramsci's perspective that contained in those work. The result of this research is the types of hegemony, including a) ideological hegemony; b) power hegemony; c) cultural hegemony; d) moral hegemony; and e) economic hegemony. Furthermore, the worldview of the author seems to integrate with the story of the characters in the novel. Abstrak: Penelitian ini difokuskan pada unsur-unsur hegemoni Gramsci pada novel Mémoires d’Hadrien karya Marguerite Yourcenar. Hegemoni Gramsci adalah suatu konsep dan strategi penguasaan berbasis kepemimpinan intelektual dan kesadaran moral yang dilandasi persetujuan. Metode dalam penelitian ini adalah metode deskriptif-kualitatif. Teknik penelitian ini menggunakan Studi Pustaka dan Studi Dokumentasi. Populasi penelitian ini adalah novel Mémoires d’Hadrien, sedangkan sampel penelitiannya adalah unsur hegemoni yang terdapat pada karya tersebut. Berdasarkan hasil kajian, hegemoni yang muncul meliputi: a) hegemoni ideologi; b) hegemoni kekuasaan; c) hegemoni budaya; d) hegemoni moral; dan e) hegemoni ekonomi. Adapun selanjutnya, pandangan dunia pengarang terlihat berintegrasi dengan cerita tokoh pada novel.